Static tests of constructive tires using hydraulic press on the soil - Machado, Thiago M.; Lanças, Kléber P. [UNESP]; De Oliveira Junior, Mauro B.; Artioli, José A.; Marasca, Indiamara [UNESP] (FapUNIFESP (SciELO), 2015)
The power consumption and load capacity of agricultural machines have grown and the effects of pressure on the soil by tires have been still little investigated. In concern with sustainable development, the relationship machine-tire-soil must be in balance to give more consistency on the best use of tires for a given load. This study aimed to evaluate four tires of two constructive types, the bias belted tires and radial tires, both with respective rim diameters of 22.5 and 26.5 inches with variables measuring the footprint, elastic deformation, sinkage and resistance to penetration. A hydraulic press with an attachment shaft for tire mounting and a box of soil in which the tire has been imposed on a load of 53.00 kN using nominal pressures recommended by the tire manufacturer. The radial construction tire with rim diameter of 26.5 inches obtained less sinkage and resistance to penetration; however, greater elastic deformation and footprint compared to other tires. The bias-belted tire with 22.5-inch rim presented the highest resistance to penetration and the lowest elastic deformation.
Keywords: Compaction; Elastic deformation; Footprint; Pressure; Sinkage